Debt and sustainable poverty reduction: A case study of Dao ethnic women in the northern midlands and mountains region of Vietnam - Van, Quan Nguyen; Kieu, Jennifer Thao Linh (Asian Journal of Economics and Empirical Research, 2025)
The purpose of this study is to explore the debt of Dao ethnic women in Vietnam and its impact on sustainable poverty reduction. A mixed-methods approach was employed, combining in-depth interviews with experts for scale development and quantitative data collection from 206 Dao women in the Northern Midlands and Mountains region of Vietnam. Parental and agricultural debt contribute to sustainable poverty reduction, while wedding debt has no significant impact as it is used for non-productive purposes. To effectively reduce poverty among ethnic women, especially in rural regions, the study concludes that priority should be given to promoting productive debt for income-generating activities and providing flexible loan terms. Wedding debt, which burdens families without creating economic benefits, should be discouraged. Improving financial literacy and fostering systemic changes to support marginalized communities are essential for sustainable poverty reduction. The study suggests that microfinance initiatives should prioritize productive loans for income-generating activities, support financial literacy programs tailored for ethnic women, and create policies that reduce the socio-cultural and economic barriers these women face. By focusing on flexible, productive debt and discouraging non-productive borrowing for ceremonies, poverty reduction efforts can be effective and sustainable in marginalized communities.